Oil prices and the Russian economy: Some simulation studies with NiGEM - Paavo Suni (The Research Institute of the Finnish Economy (ETLA), 2007)
Russia has greatly benefited both from exporting more energy commodities in volume terms and from the improvement of it's terms of trade due to the rise in oil and other commodity prices in the 2000's. To study the impacts, the counterfactual simulation for the years 2001-2006 and the “usual” oil price rise simulations for the future were made. According to the counterfactual simulations, the role of oil has been a key driver in the recent Russian economic development in the 2000's. The average GDP growth in 2001-6 would have been around 4 per cent, around 2.5 percentage points lower than in the actual case. The effect was strongest in the last years of the period bringing the growth even below one per cent in 2006 instead of more than 6 per cent. The strong effect is due to large and rising price difference between the actual and counterfactual oil prices especially in the years 2003-6, which would have meant pronouncedly smaller oil income into the economy than actually took place. In the other simulations, the effects of the permanent 20 USD price rise to the baseline was compared. The economy reacted initially strongly to the shocks with e.g. raising GDP growth and current account strongly. The effect was, however, quickly vanishing after the rise. The temporary end of the current commodity boom would cause serious difficulties in the Russian economic development as the fuel for the engine would dry. The more robust growth would necessitate drastic changes in the economic structure from resource based economy towards more normal economic structure. Given the short and rather undeveloped Russia time series and from this reason also rather undeveloped models, the results contain large uncertainty. However, simulations provide one useful benchmark on the size of the effects of the energy price rise on the Russian economy.
Keywords: Q32; Q43; F47; 330; Russian economy; simulation; oil price; Mineralölpreisschock; Wirtschaftswachstum; Spillover-Effekt; Simulation; Russland